IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KOTA SERANG NOMOR 2 TAHUN 2010 DALAM MENANGANI PENGEMIS DI KOTA SERANG - Handito, Rama; Hartoko, Gatot; Saepudin, Eli Apud (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The phenomenon of increasing the number of beggars in the public space of Serang City reflects the weak effectiveness of the implementation of Serang City Regional Regulation Number 2 of 2010 concerning the Prevention, Eradication, and Control of Community Diseases. This study aims to describe the implementation of the policy and identify the obstacles faced by the Regional Government in its implementation. This research uses a descriptive qualitative method. The data collection technique was carried out through observation, interviews and documentation of informants from the Social Service, Satpol PP, beggars and the people of Serang City. The results of the study show that policy implementation is still not optimal, characterized by weak coordination between agencies, lack of human resources and budget, low intensity of socialization to the community, and low public awareness in complying with regulations. In addition, social rehabilitation programs for beggars have not been effective and tend to be charitative, so they have not touched the root of the problem. This study recommends the need to improve cross-sector coordination, optimize socialization, a sustainable empowerment approach, and firm and measurable law enforcement. These findings are expected to be evaluation material for local governments in formulating a more humane, sustainable, and participatory strategy for handling beggars